Influence of Coarse Aggregate Geometry and Mineral Composition on the Durability of Asphalt Concrete - Mohammad, Hussein K.; Albayati, Amjad H.; Al-Kheetan, Mazen J. (Infrastructures (Basel), 2025)
The durability of asphalt concrete is highly dependent on the geometry and mineralogy of coarse aggregates, yet their combined influence on mechanical and moisture resistance properties is still not fully understood. This study evaluates the effects of coarse aggregate geometry, specifically flat and elongated particle ratios and angularity, as well as mineral composition (quartz versus calcite), on asphalt mixture durability. The durability of mixtures was evaluated through Marshall properties as well as moisture susceptibility indicators, including the tensile strength ratio (TSR) and index of retained strength (IRS). Statistical analyses (ANOVA and t-tests) were also conducted to confirm the significance of the observed effects. Results showed that mixtures containing higher proportions of flat and elongated particles exhibited greater void content, reduced stability, and weaker moisture resistance, with the 1:5 flat-to-elongated ratio showing the most adverse impact (TSR 73.9%, IRS 69.2%). Conversely, increasing coarse aggregate angularity (CAA) enhanced mixture performance, with TSR values rising from 63.5% at 0% angularity to 81.2% at 100% angularity, accompanied by corresponding improvements in IRS. Mineral composition analysis further demonstrated that calcite-based aggregates achieved stronger bonding with asphalt binder and superior resistance to stripping compared to quartz-based ones. These findings confirm that aggregate geometry and mineralogy exert a decisive influence on asphalt mixture durability. They also highlight the need to revise current specifications that permit the use of uncrushed coarse aggregate in asphalt base courses, particularly when such layers may serve as surface courses in suburban or low-volume roads, where long-term resistance to moisture damage is critical.